ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2013 - admin, EMA AGUSTINA LIAWATI B11111050 (Jurnal Manajemen Update, 2016)
The purpose of this research to analysis the influence companyâ€™s internal factors (profitability, business risk and firm size) on capital structure in the Basic and Chemical industry sector which are listed in Indonesian Stock Exchange in 2010-2013 period. Sample in this research are 23 companies selected by purposive sampling. Independent variables in this research are profitability (ROA), business risk (DOL) and firm size (Ln Total Asset) and dependent variable is capital structureÂ  (DER). The data used are secondary received from BEI data base. Collected data are than analyzed by using multiple regression analysis (t test, F test and the coefficient of determination) and by the classical assumption that includes test of normality, linearity, multikolinearity, autocorrelation and heterokedastisitas. The results of this research show that profitability (ROA) effect negative and significant on capital structure. Business risk (DOL) effect negative and not significant on capital structure. Firm size (Ln total asset) effect positive and significant on capital structure. In partially, profitability (ROA), business risk (DOL) and firm size (Ln Total asset) are significant on capital structure (DER) with value of calculate F 9,847 and sig value 0,000 < 0,05. From the coefficient of determination test show 25,1% independent variable influence dependent variable and residue is influenced by other variable are not form in model or variable. Keywords : Capital Structure, Profitability, Business Risk and Firm Size